Estudio del patrimonio gastronómico y su aporte en el desarrollo turístico del cantón san francisco de Pueblo Viejo - Rendón Vizcaíno, Shirley Lilibeth (2016)
The loss of the Gastronomic Heritage in the San Francisco Canton of Puebloviejo, a province of the rivers, is a worrying and transcendental issue because of its importance in the contribution of tourism development, worthy of being investigated, with the objective of determining the causes of its disappearance It is concluded that the problem of the disappearance is due to the lack of knowledge of the inhabitants, as well as the lack of interest of the corresponding authorities to preserve the gastronomic heritage that is Fundamental for the tourist development of the Canton San Francisco de Puebloviejo. It is here when the idea of proposing the creation of a website, which will provide information on the main typical Creole dishes of the Canton San Francisco de Puebloviejo, is proposed, which will have as its purpose to revitalize the gastronomic customs of the locality, providing information to the inhabitants Which sell gastronomy and those who wish to dedicate themselves to the sale of it, developing an image that allows to identify the Gastronomic Heritage enriching tourism development